Optimization of Inspection Routes Using Linear Programming & Nearest Neighbour at KJPP ANA & Rekan Gianyar - Canigia Susila, Ni Made Ari; Penindra, I Made Dwi Budiana; Utami, Ni Made Cyntia; Ariyani, Ni Wayan Sri; Juliana, Mia; Sitanggang, Bryan Estavan Imanuel (Bulletin of Science Education, 2024)
Inspection is the activity procedures of an appraiser identical with survey to the location of the object of assessment. Considering efficient KJPP ANA & Rekan Gianyar is important for determining the best route in order to reduce overtime. This research focused in optimizing the inspection case route to the location using Linear Programming (LP) and Nearest Neighbor (NN) for Traveling Salesman Problem cases. In addition, analyzing the comparison of the initial route and the new route with both methods after optimizing travel time to reduce overtime. This research combined set theory and distribution & transportation concepts in the optimization. The data in this research used primary data including initial route along with the coordinates and secondary includes company profiles, LP and NN algorithms collected through interviews, documentation and literature study. The collected data were processed with Microsoft Excel and Google Colaboratory software. The results found that the LP method minimized travel time savings by an average of 12%, while the NN method is 8%. The LP method minimized the average overtime and costs by 16 minutes (Rp. 13,000, -) while the NN method is 11 minutes (Rp. 9,000, -). Keywords: Linear programming, Nearest neighbor, Route optimization, Traveling salesman problem